On discordance test for the wrapped normal data - Adzhar Rambli; Ibrahim Mohamed; Abdul Ghapor Hussin; Safwati Ibrahim (Universiti Kebangsaan Malaysia, 2012)
This paper focuses on detecting outliers in the circular data which follow the wrapped normal distribution. We considered four discordance tests based on M, C, D and A statistics. The cut-off points of the four tests were obtained and the performance of the detection procedures was studied via simulations. In general, we showed that the discordance test based on the A statistic outperforms the other tests in all cases. For illustration, the city of Kuantan wind direction data set was considered.